2017
DOI: 10.1167/iovs.16-20922
|View full text |Cite
|
Sign up to set email alerts
|

HTRA1 and TGF-β1 Concentrations in the Aqueous Humor of Patients With Neovascular Age-Related Macular Degeneration

Abstract: In nCNV patients, HTRA1 and TGF-β1 were significantly higher compared to controls. After treatment, TGF-β1 was persistently elevated, while HTRA1 returned to control levels, suggesting the involvement of TGF-β1 and HTRA1 in neovascular AMD and a VEGFA-independent role for TGF-β1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 30 publications
0
36
0
Order By: Relevance
“…A study of the mice model of arthritis also showed the increase in HtrA1 expression (Hou et al, 2013). Furthermore, HtrA1 is implicated in Age-related macular degeneration (AMD) (Horie-Inou & Inou, 2014;Tosi et al, 2017) and it is now widely accepted that inflammation and the immune system plays important roles in AMD pathogenesis (Iannaccone et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A study of the mice model of arthritis also showed the increase in HtrA1 expression (Hou et al, 2013). Furthermore, HtrA1 is implicated in Age-related macular degeneration (AMD) (Horie-Inou & Inou, 2014;Tosi et al, 2017) and it is now widely accepted that inflammation and the immune system plays important roles in AMD pathogenesis (Iannaccone et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…As the most potent pro-angiogenic factor recognized internationally so far, VEGF can enhance the microvascular permeability, increase the release of tissue factors and proteases and stimulate division of endothelial cells. TGF-β1 directly regulates VEGF expression and participates in CNV (19)(20)(21). According to the results in this study, obviously reduced concentrations of serum VEGF and TGF-β1 were observed after combination therapy, implying that the disease is controlled efficiently, and the visual acuity is improved.…”
Section: Discussionmentioning
confidence: 57%
“…Aflibercept and ranibizumab are recombinant humanized monoclonal antibodies that inactivate VEGF (22). VEGF is a potent angiogenic factor, the overexpression of which is known to deteriorate AMD (23). TGF-β1, a critical regulator in various physiological and pathological processes, stimulates endothelial cells to synthesize as well as secrete VEGF.…”
Section: Discussionmentioning
confidence: 99%